2018
DOI: 10.3390/rs10040525
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet-Based Rust Spectral Feature Set (WRSFs): A Novel Spectral Feature Set Based on Continuous Wavelet Transformation for Tracking Progressive Host–Pathogen Interaction of Yellow Rust on Wheat

Abstract: Understanding the progression of host-pathogen interaction through time by hyperspectral features is vital for tracking yellow rust (Puccinia striiformis) development, one of the major diseases of wheat. However, well-designed features are still open issues that impact the performance of relevant models to nondestructively detect pathological progress of wheat rust. The aim of this paper is (1) to propose a novel wavelet-based rust spectral feature set (WRSFs) to uncover wheat rust-related processes; and (2) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…Remote sensing has become a feasible technology for disease detection and assessment over the last several decades. Diseases that have been detected using remote sensing include rust infection [6][7][8], Fusarium head blight [9,10], and powdery mildew [9][10][11][12] in wheat, bacterial leaf blight in rice [13,14], grey leaf spot in maize [15], and late blight disease and bacterial spot in tomato [16,17]. When plants are infected with diseases, the leaf water, pigment content and internal structure undergo changes, and these biochemical and biophysical changes are also reflected in the spectral characteristics of plants [18].…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing has become a feasible technology for disease detection and assessment over the last several decades. Diseases that have been detected using remote sensing include rust infection [6][7][8], Fusarium head blight [9,10], and powdery mildew [9][10][11][12] in wheat, bacterial leaf blight in rice [13,14], grey leaf spot in maize [15], and late blight disease and bacterial spot in tomato [16,17]. When plants are infected with diseases, the leaf water, pigment content and internal structure undergo changes, and these biochemical and biophysical changes are also reflected in the spectral characteristics of plants [18].…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of CWA for the hyperspectral-data-based identification and detection of crop pests and diseases has been demonstrated [14][15][16][17]20]. Continuous wavelet transform (CWT) [39] is a wavelet analysis method for localizing the signal simultaneously in the time-frequency domain to detect and analyze weak signals at various scales and resolutions and to analyze multidimensional hyperspectral signals across a scale continuum [14,16,40]. Based on CWT, the original reflectance spectrum of each Fusarium-head-blight-infected ear is first converted to a wavelet coefficient spectrum set on multiple scales with a mother wavelet function, in which each scale corresponds to a frequency of spectral change: high scale corresponds to low frequency and low scale corresponds to high frequency.…”
Section: Wavelet Features Extraction For Fusarium Head Blight Using Cwamentioning
confidence: 99%
“…For instance, Zhang et al [14] accurately estimated the disease severity of powdery mildew on leaf level through the combination of CWA and partial least square regression. Zhang et al [15] and Shi et al [16] revealed the promising potential of CWA for the identification of wheat yellow rust. By using CWA, Luo et al [17] quantified wheat aphid infestation successfully.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous wavelet analysis (CWA) is an effective noise reduction method and it can also enhance the details of spectral features of hyperspectral data [39][40][41]. Hence, CWA has been successfully utilized in quantitative remote sensing for retrieving functional traits of plants (e.g., leaf mass per area [42], canopy water content [43], leaf dry matter content and specific leaf area [44]).…”
Section: Introductionmentioning
confidence: 99%